Nurse-led home-visitation programme for first-time mothers in reducing maltreatment and improving child health and development (BB:2-6): longer-term outcomes from a randomised cohort using data linkage. Issue 2 (10th February 2022) - Robling, Michael; Lugg-Widger, Fiona V; Cannings-John, Rebecca; Angel, Lianna; Channon, Sue; Fitzsimmons, Deborah; Hood, Kerenza; Kenkre, Joyce; Moody, Gwenllian; Owen-Jones, Eleri; Pockett, Rhys D; Sanders, Julia; et al.
Abstract : Objectives: Measure effectiveness of family nurse partnership (FNP) home-visiting programme in reducing maltreatment and improving maternal health and child health, developmental and educational outcomes; explore effect moderators, mediators; describe costs. Design: Follow-up of BB:0–2 trial cohort (ISRCTN:23019866) up to age 7 years in England using record linkage. Participants: 1618 mothers aged 19 years or younger and their firstborn child(ren) recruited to BB:0–2 trial at less than 25 weeks gestation and not mandatorily withdrawn from trial or opted out. Intervention families were offered up to a maximum of 64 home visits by specially trained nurses from pregnancy until firstborn child was 2 years old, plus usually provided health and social care support. Comparator was usual care alone. Outcome measures: Primary outcome: state-verified child-in-need status recorded at any time during follow-up. Secondary outcomes: referral to social services, child protection registration (plan), child-in-need categorisation, looked-after status, recorded injuries and ingestions any time during follow-up, early childcare and educational attendance, school readiness and attainment at key stage 1 (KS1), healthcare costs. Results: Match rates for 1547 eligible children (1517 singletons, 15 sets of twins) were 98.3% (NHS Digital) and 97.4% (National Pupil Database). There was no difference between study arms in the proportion of children being registered as in need (adjusted OR 0.98, 95% CI 0.74 to 1.31), or for any other measure of maltreatment. Children in the FNP arm were more likely to achieve a good level of development at reception age (school readiness) (adjusted OR 1.24, 95% CI 1.01 to 1.52). After adjusting for birth month, children in FNP arm were more likely to reach the expected standard in reading at KS1 (adjusted OR 1.26, 95% CI 1.02 to 1.57). We found no trial arm differences for resource use and costs. Conclusions: FNP did not improve maltreatment or maternal outcomes. There was evidence of small advantages in school readiness and attainment at KS1. Trial registration number: ISRCTN23019866 .